2008
DOI: 10.1111/j.1540-8191.2008.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance of Stentless Versus Stented Valves: A Systematic Review and Meta-Analysis

Abstract: Stentless valves did not display hemodynamic benefit in terms of LV mass regression or postoperative mean gradients, but do appear to display superior hemodynamics in terms of peak gradients. Further well-designed and adequately powered trials are required to fully address this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…In our hands, the valve proved to be versatile and has demonstrated good intra-operative handling characteristics. Early hemodynamic data are encouraging and are comparable with conventional stented valves [15,[18][19][20][21][22]. The effective orifice area, indexed effective orifice area, cardiac output, and cardiac index exhibited a slight decrease over the follow-up period, which is consistent with reports on other stented valves [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our hands, the valve proved to be versatile and has demonstrated good intra-operative handling characteristics. Early hemodynamic data are encouraging and are comparable with conventional stented valves [15,[18][19][20][21][22]. The effective orifice area, indexed effective orifice area, cardiac output, and cardiac index exhibited a slight decrease over the follow-up period, which is consistent with reports on other stented valves [18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 88%
“…The bypass and aortic cross-clamp times reported in the present series are shorter, but not statistically different from those reported for other stented bioprostheses [15,18,19]. It is important to note, however, that procedural time relates inversely with the experience of the surgical team, and data from experienced centers indicate that the above times can be significantly reduced to as low as 36.8 AE 7.7 and 54.8 AE 11.5 min for stand-alone procedures, respectively.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A third trial (ASSERT) compared Medtronic Mosaic porcine xenograft stentless versus Freestyle porcine xenograft stented prostheses and found that the stentless group had lower peak gradients and larger EOAs 23. A further meta-analysis showed that although stentless valves had lower peak gradients, they did not have lower mean gradients 6. Cohen et al recently published long-term (10-year) follow-up data comparing the Carpentier-Edwards bovine pericardium stented and the Toronto porcine xenograft stentless prostheses and found superior haemodynamics (larger EOAs and lower gradients) in the stentless group 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indeed demonstrated that stentless bioprostheses have lower gradients and greater effective orifice areas (EOAs) compared with stented bioprostheses 3–5. A meta-analysis, however, showed that different haemodynamic parameters may give differing results: although stentless valves had lower peak gradients, they did not display lower mean gradients 6. Published data on EOAs may also be confounded by inaccuracies in measurements of the left ventricular outflow tract diameter (LVOTd), non-indexation to body surface area (BSA) and differences in prosthesis sizes.…”
Section: Introductionmentioning
confidence: 99%